REVIEWING THE USE OF TELEVISION SHOWS FOR LEARNING AND TEACHING OF ENGLISH LANGUAGE AND LITERATURE: POTENTIALS AND LIMITATIONS - Karunia Eka Nafilatul Janah (Universitas Muhammadiyah Semarang, 2021)
As technology innovation grows rapidly, teaching media related to the use of technology for English learning and teaching are also more varied. One of teaching media related to the use of technology is using television shows for learning and teaching. This paper aims to review the use of television shows for learning and teaching of English language and literature. Besides, this paper also discusses the potentials and limitations of using television shows for language learning and teaching. There are some activities using the television shows, such as asking the students to describe elements of literature in the television shows, explain the language features that probably appear in the television shows, and many others. Furthermore, the students’ listening and writing skills can be improved through those activities. Students can also be taught cultural aspects of the television shows. The good impacts of using television shows are improving children’s ability to recall story plots, crucial details, and abstract problem-solving skills, affecting students’ higher grades in English, mathematics, and science, increasing students’ leisure-time for reading books, and improving students’ academic performance and self-esteem. The limitation of using television shows for language learning and teaching can be found in the difficulty of finding the television shows that use English. Then, related to cultural contents, English teachers have to make sure that the television shows have appropriate scenes to watch. Lastly, using television shows for learning and teaching needs more preparation and special assistance. Therefore, teachers have to be careful in utilizing television shows for language learning and teaching so that the limitations can be minimized and the potentials can be increased.